2016
DOI: 10.1007/s00345-016-1801-y
|View full text |Cite
|
Sign up to set email alerts
|

The importance of clinical stage among patients with a complete pathologic response at radical cystectomy after neoadjuvant chemotherapy

Abstract: Patients without evidence of disease at the time of RC are still at risk of recurrence and death from bladder cancer. Higher clinical stage and increased time to RC were associated with an increased risk of recurrence and subsequent death. These data highlight the importance of timely RC and the continued risk of recurrence in higher clinically staged patients-underscoring the need for close monitoring and patient counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A number of previous studies have demonstrated that the tumor staging of BLCA has a crucial effect on the clinical characteristic of patients [37,38], such as overall survival time, chemotherapy response, and tumor recurrence. In addition, various molecular markers were also identified as important targets for clinical usage [39].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have demonstrated that the tumor staging of BLCA has a crucial effect on the clinical characteristic of patients [37,38], such as overall survival time, chemotherapy response, and tumor recurrence. In addition, various molecular markers were also identified as important targets for clinical usage [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that a less stringent follow-up regimen could be applied to patients with pCR after RC [ 55 ]. However, pT0 did not mean a patient was free of bladder cancer [ 56 ]. Previous studies have shown that pT0 patients have lower disease-specific mortality; nonetheless, there are still pT0 patients who die from bladder cancer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%